Walking With Elephants: A Case for Trans-Species Ethnography - Erickson, Jonathan (The Trumpeter)

(untitled) (Athabasca University Press, 2017)
This paper argues for the development of new methodologies for studying animals and human-animal relationships that take qualitative and hermeneutic considerations into account. Drawing on the traditions of anthropology, depth psychology, and somatic studies, the paper advocates for the use of a trans-species ethnography that situates the researcher as a participant-observer in the field, in relationship with the subjects of study. This theoretical framework is illustrated by case study in the form of the author’s fieldwork on human-elephant communication at an elephant sanctuary in Cambodia.